Heavy Metal Stress-Responsive Phyto-miRNAs - ÇELİK, ÖZGE; AYAN, ALP; MERİÇ, SİNAN; ATAK, ÇİMEN (Springer Science and Business Media B.V., 2020)
Heavy metal stress is a leading abiotic stress factor in the twenty-first century as a reflection of industrial developments and extensive urbanization. Plants adopt several adaptation mechanisms to cope with deleterious effects of heavy metal stress. Biosynthesis of amino acids/organic acids, phytochelatins (PCs), metallothioneins (MTs), heat-shock proteins (HSPs), metal chelators, chaperons, ABC-type transporters, and CDF family metal transporters are among the heavy metal binding or transporting mechanisms in plants. This chapter emphasizes phyto-miRNAs related to these tolerance mechanism pathways. Moreover, transcription factors which are targeted by heavy metal-related phyto-miRNAs are also summarized under the effect of various heavy metals due to their intertwined regulatory mechanisms.
Keywords: Heavy Metal Stress; Gene Expression Regulation; Phyto-miRNAs; Metal-binding Proteins